Electron and Positron Collision with Neon at Intermediate Energies - and S. Saxena3, Keshav R. Verma1*, Kamlesh K. Sharma2 (Recent Research in Science and Technology, 2011)
In present paper differential scattering cross section and total scattering cross section for the first excited state of neon by electron as well as positron are reported and comparison is made with different available theoretical and experimental data. The present calculation is done with R matrix theory. We have chosen a complex type potential, a part of which is directly calculated from the target charge density and other part is taken from Baluja and Jain. The present work yields a satisfactory result for differential cross section while previously large discrepancies were found in theoretical and experimental data. More positron results are required for the best judgment of present calculation.